Preliminary Study of Cellulose Insulation Material from Oil Palm Tree Fiber - Nur Amirah Elias; Siti Amira Othman; Nur ‘Izqa Ashiqin Mohd Najib; Siti Nursyakirah Idris; Fong Chui Nee (Multidisciplinary Applied Research and Innovation, 2023)
Cellulose insulation is one of the most environmentally friendly types of insulation. Recent research on cellulose suggests that it might be an effective solution for reducing fire damage. Because of the material’s compactness, cellulose contains no oxygen. Since there is no oxygen in the material, the amount of damage caused by a fire is reduced. As a result, cellulose is not only one of the most environmentally friendly kinds of insulation, but it is also one of the most fire-resistant kinds of insulation. Following that, cellulose insulation is somewhat more mold resistant than fiberglass and certain other materials. It is a prevalent misperception that crude borates in cellulose insulation give the product pest control qualities. As a result, cellulose is a low-cost and effective insulator.